2021
DOI: 10.3892/ijmm.2021.4983
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on prenatal polychlorinated biphenyl exposure and the development of the progeny nervous system (Review)

Abstract: The developmental origins of health and disease concept illustrates that exposure in early life to various factors may affect the offspring's long-term susceptibility to disease. during development, the nervous system is sensitive and vulnerable to the environmental insults. Polychlorinated biphenyls (PcBs), which are divided into dioxin-like (dL-PcBs) and non-dioxin-like PcBs (NdL-PcBs), are synthetic persistent environmental endocrine-disrupting chemicals. The toxicological mechanisms of dL-PcBs have been as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 124 publications
(166 reference statements)
0
3
0
Order By: Relevance
“…Another mechanism for the decrease in serumT4 concentrations in both adults and neonates may be the ability of PCBs to induce hepatic microsomal enzymes leading to biliary excretion and elimination of the thyroid hormones. Such changes could be particularly adverse during early pregnancy and even have long-term effects on the brain, as demonstrated in Table 2 [ 3 , 153 , 154 , 155 , 156 , 157 , 169 , 170 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism for the decrease in serumT4 concentrations in both adults and neonates may be the ability of PCBs to induce hepatic microsomal enzymes leading to biliary excretion and elimination of the thyroid hormones. Such changes could be particularly adverse during early pregnancy and even have long-term effects on the brain, as demonstrated in Table 2 [ 3 , 153 , 154 , 155 , 156 , 157 , 169 , 170 ].…”
Section: Resultsmentioning
confidence: 99%
“…From observational studies, there is strong evidence that TDCs are disturbing the thyroid hormone metabolism (s. Table 2 ). This is reported for several classes of TDCs, for mother-child pairs, in case controls, smaller cohorts or larger epidemiological studies [ 6 , 102 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 18...…”
Section: Resultsmentioning
confidence: 99%
“…While maybe less understood at the molecular level, it is worth mentioning given its historical importance the case of dioxins for which a wide literature exists following the Seveso catastrophe, when in 1976, a chemical plant accidentally released a dioxin derivative, the TCDD (2, 3, 7, 8-tetrachlorodibenzo-p-dioxin), triggering the death of tenths of thousands of farm animals, either by the emanations or by slaughtering, while 193 children suffered from chloracne induced by the chemical. Several papers indicated that dioxin influences the development of the nervous system, as recently reviewed [ 129 ]. As an interface to the fetal organs, the placenta is particularly interesting to understand how fetal organs might be touched by the molecule.…”
Section: Mechanisms Of Oxidative Stress Induction By Environmental Pollutantsmentioning
confidence: 99%